Evaluation of forage yield performance in advanced generations of a timothy "clone and strain synthesis" strain. (26th November 2013) - Tanaka, Tsuneki; Tamaki, Hiroyuki; Ashikaga, Kazunori; Fujii, Hiroki; Sato, Koichi; Iwabuchi, Kei; Adachi, Mieko
Abstract Clone and strain synthesis (CSS) is similar to variety synthesis to boost improvement of yield in perennial self‐incompatible forage grasses such as timothy (Phleum pratense L.). This study was undertaken to investigate the scale of inbreeding depression in advanced generations of CSS. The second to fourth synthetic generations (Syn2–4) of timothy CSS strain, 'Kitakei 04306, ' were compared for cumulative annual dry matter yields (DMYs) and some agro‐morphological characteristics of 2009–2011. No significant difference was found among the generations for any examined characteristic, aside from a slight yield decrease (–1.7% for Syn2–4) with the advance of generations. Furthermore, DMY of Syn4, corresponding to a generation propagated as commercial seeds, remained 9.0% higher than that of its pollen parent. These results indicate the yield superiority of 'Kitakei 04306.' A risk of severe yield decrease in CSS could not be shown in our limited experiments.